2014
DOI: 10.1111/jvs.12190
|View full text |Cite
|
Sign up to set email alerts
|

Which is a better predictor of plant traits: temperature or precipitation?

Abstract: Question: Are plant traits more closely correlated with mean annual temperature, orwithmean annual precipitation? Location: Global. Methods: We quantified the strength of the relationships between temperature and precipitation and 21 plant traits from 447,961 species-site combinations worldwide. We used meta-analysis to provide an overall answer to our question. Results: Mean annual temperature was significantly more strongly correlated with plant traits than was mean annual precipitation. Conclusions: Our stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

51
329
10
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 375 publications
(398 citation statements)
references
References 146 publications
51
329
10
8
Order By: Relevance
“…Compared with SLA and LDMC, higher variation in LA and LT among co-existing species within a site (> 49%, Figure 4) may result in relatively weak spatial variation. Similarly, in an analysis of global leaf traits, Moles et al (2014) found that the majority of variation occurred at the local scale or within communities, e.g., 34% for plant height and 43% for LA. The larger variance occurring within sites may be the result of micro-site variability, phylogenetic or historical effects, or biotic interactions and competition (Ordonez et al, 2010).…”
Section: Latitudinal Variation In Species-level Leaf Traits and The Cmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared with SLA and LDMC, higher variation in LA and LT among co-existing species within a site (> 49%, Figure 4) may result in relatively weak spatial variation. Similarly, in an analysis of global leaf traits, Moles et al (2014) found that the majority of variation occurred at the local scale or within communities, e.g., 34% for plant height and 43% for LA. The larger variance occurring within sites may be the result of micro-site variability, phylogenetic or historical effects, or biotic interactions and competition (Ordonez et al, 2010).…”
Section: Latitudinal Variation In Species-level Leaf Traits and The Cmentioning
confidence: 99%
“…Through regulating the metabolic activity and carbon allocation of plants (Moles et al, 2014), climate directly influences the morphology of leaves. In addition, climate may influence the geographic distribution of leaf traits indirectly by shaping the biogeography of the vegetation as well as soil nutrient availability (Chapin et al, 2002;Ordonez et al, 2009).…”
Section: Latitudinal Variation In Species-level Leaf Traits and The Cmentioning
confidence: 99%
See 1 more Smart Citation
“…For LES rules to work in biospheric models, relationships between the key plant traits must be consistent (or at least known) across prevailing environmental conditions, such as climate and substrate fertility (7,8). However, the geography of-and thus the geophysical controls over-LES traits remain poorly understood (9).…”
mentioning
confidence: 99%
“…, 为有效地加强植物 体内的水分运输与利用效率和进一步增强现实竞争 力, 植物在叶片的叶肉组织和叶脉网络系统的构造 上进行权衡投资 (Wilson et al, 1999;Reich & Cornelissen, 2014), 促使植物调整叶脉结构和叶片厚度 的生物量分配和叶片构型构建, 从而提高植物对土 壤水分的有效利用 (Moles et al, 2014;王瑞丽等, 2015), 实现叶片生理特性和环境空间异质性的精 (1)植物光合参数测定。于8月15-18日(代表植 物生长旺盛期), 选择晴朗天气的9:00-12:00进行气…”
unclassified